2022
DOI: 10.1186/s12889-022-12502-8
|View full text |Cite
|
Sign up to set email alerts
|

Global school-based student health survey: country profiles and survey results in the eastern Mediterranean region countries

Abstract: Background The increasing prevalence of non-communicable diseases (NCDs) has some major implications on many countries to achieve universal health coverage. This study aimed to investigate the implementation of Global School-based Student Health Survey (GSHS), which is used to assess the risk factors of NCDs among children and adolescents in the eastern Mediterranean region (EMR). Methods This study was a meta-analysis and systematic literature rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The interest in NCDs is expanding, and can be seen from various viewpoints. Multiple literature revisions showed that several studies have been published on this topic over the years, not only on NCDs themselves [ 17 , 18 ], but also on the effects of lifestyle changes on NCDs [ 19 ], socioeconomic inequalities [ 20 ], and the development of new indicators [ 21 ]. Aside from looking at longer and shorter periods, the published evaluations looked at various databases primarily covering health and social science, while sectors such as engineering were left out, and could potentially be a source of additional data [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The interest in NCDs is expanding, and can be seen from various viewpoints. Multiple literature revisions showed that several studies have been published on this topic over the years, not only on NCDs themselves [ 17 , 18 ], but also on the effects of lifestyle changes on NCDs [ 19 ], socioeconomic inequalities [ 20 ], and the development of new indicators [ 21 ]. Aside from looking at longer and shorter periods, the published evaluations looked at various databases primarily covering health and social science, while sectors such as engineering were left out, and could potentially be a source of additional data [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In light of these facts, our study was conducted to estimate the prevalence of bullying and to explore the associated factors using an adapted Arabic version of an internationally recognized questionnaire (GSHS) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…WHO stepwise methodology and pre-designed questionnaire was used for data collection. Participant's information such as socio-demographic details and risk factors behavior for cardiovascular disease were collected based on the Global School Health Survey questionnaire [13]. Blood pressure and nutritional status was evaluated by mercury sphygmomanometer and anthropometric measurements respectively.…”
Section: Methodsmentioning
confidence: 99%